Answer:
The equation of parabola is:
![y=(1)/(2)x^2+(-2)x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4zkzkn5skbvwbqkrx2tsa36uxrff2dd6h5.png)
Explanation:
We know that the vertex form of the equation of parabola is given by:
![y=a(x-h)^2+k](https://img.qammunity.org/2020/formulas/mathematics/high-school/7xiq973pej7bis77rj649g420rebwvc4wx.png)
where the vertex of the parabola is (h,k).
Now, from the graph i.e. provided to us we see that the vertex of the parabola is located at (2,-1)
i.e.
(h,k)=(2,-1)
i.e.
h=2 and k= -1
Hence, we have the equation of the parabola as:
![y=a(x-2)^2+(-1)\\\\i.e.\\\\y=a(x-2)^2-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rxsaxlbv5pfu44u9o6n8gpjeta3igm6nli.png)
Now, with the help of a passing through point of the parabola we may easily obtain the value of a.
The parabola passes through (0,1)
Hence, on putting x=0 and y=1 we have:
![1=a(0-2)^2-1\\\\i.e.\\\\1=a* 4-1\\\\i.e.\\\\4a-1=1\\\\i.e.\\\\4a=1+1\\\\i.e.\\\\4a=2\\\\i.e.\\\\a=(2)/(4)\\\\i.e.\\\\a=(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ba2fokcfchxby63vo4n6hhmnldauuvqszg.png)
Hence, the equation of parabola will be:
![y=(1)/(2)(x-2)^2-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aj4otiyqv5rnkglrajvohs2ixcne3msia0.png)
On expanding the square term we have:
![y=(1)/(2)(x^2+(-2)^2-2* x* 2)-1\\\\i.e.\\\\y=(1)/(2)(x^2+4-4x)-1\\\\i.e.\\\\y=(1)/(2)x^2+(1)/(2)* 4+(1)/(2)* (-4x)-1\\\\i.e.\\\\y=(1)/(2)x^2+2-2x-1\\\\i.e.\\\\y=(1)/(2)x^2-2x+2-1\\\\i.e.\\\\y=(1)/(2)x^2-2x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/26v9keos6lfi0towepxj8dlsdnqvxnlow1.png)